The Effect of Gender Equality on Work Performance, Career Development with Organizational Culture as an Intervening Variable (Case Study: Civil Servants in Medan City) - Sjukun; Siagian, Supriadi (Journal of Global Business and Management Review, 2024)
Gender Equality is a very important social issue and is widely discussed in various circles, especially in an organization. Gender equality is applied due to gender discrimination revolving around the inequality of opportunities that employees have in improving work performance and developing careers in a company organization, both private and government companies, especially female workers or employees. The purpose of this study is to analyze the effect of gender equality on work performance, career development with organizational culture as an intervening variable (case study: Medan city civil servants. The data collection method for this study is in the form of a questionnaire that will be distributed to civil servants in Medan City using Likert Scale Measurement. The population in this study were all employees who work as civil servants in the Medan City area. The population of civil servants in Medan City in 2023 is 10318 spread across all government agencies in Medan City. This study uses snowball sampling, the number of samples in this study is 385 samples. The data analysis method uses quantitative descriptive analysis, namely by distributing online and offline questionnaires. Data analysis using SEM-PLS and SPSS software version 24. The results of the study indicate that gender equality affects work performance through organizational culture and gender equality affects career development through organizational culture